Correlates of repeat pregnancies among adolescent girls and young women in sub-Saharan Africa - Bright Opoku Ahinkorah; Richard Gyan Aboagye; Joshua Okyere; Abdul-Aziz Seidu; Eugene Budu; Sanni Yaya (BMC, 2023)
Abstract Background Adolescent girls and young women are vulnerable populations who are at risk of several adverse sexual and reproductive health outcomes, including unintended pregnancies, sexually transmitted infections, unsafe abortions, and death from pregnancy-related complications. In this study, we examined the correlates of repeat pregnancies among adolescent girls and young women in sub-Saharan Africa (SSA). Methods We extracted data from the most recent Demographic and Health Surveys (DHS) of 31 countries in SSA. Countries whose surveys were conducted from 2010 to 2020 were included in the study. A total of 108,572 adolescent girls and young women (15-24 years) were included in the study. We used a multilevel mixed-effect binary logistic regression analysis to examine the correlates of repeat pregnancies among adolescent girls and young women in SSA. Results We found that adolescent girls and young women aged 20-24 [aOR = 2.36; 95%CI = 2.22, 2.51], those married [aOR = 7.52; 95%CI = 6.81, 8.30], living with a partner [aOR = 7.51; 95%CI = 6.87, 8.21], and those who had sexual intercourse before age 20 [aOR = 1.41; 95%CI = 1.33, 1.51] had higher odds of experiencing repeat pregnancies compared to those aged 15-19, those never in a union, those whose first sexual intercourse occurred at age 20 and above, respectively. Respondents exposed to listening to radio [aOR = 1.12; 95%CI = 1.06, 1.18] and those who justified intimate partner violence [aOR=1.13; 95%CI = 1.07, 1.19] had higher odds of experiencing repeat pregnancies compared to those who never listened to radio and those who did not justify intimate partner violence, respectively. Young women who had attained secondary or higher educational level [aOR = 0.83; 95%CI = 0.78, 0.90], those exposed to reading newspaper or magazine [aOR = 0.90; 95%CI = 0.82, 0.98], those residing in rural areas [aOR = 0.92; 95%CI = 0.86, 0.98], and those belonging to the richer [aOR = 0.87; 95%CI = 0.80, 0.95] and richest [aOR = 0.68; 95%CI = 0.61, 0.76] wealth quintile were less likely to experience repeat pregnancies. Conclusion The correlates of repeat pregnancies include age, age at first sexual intercourse, marital status, exposure to media, justification of intimate partner violence, wealth index, educational attainment, and place of residence. The findings underscore the need for governments and policymakers in SSA to implement policies that target the most at-risk groups: those with no formal education, the poor, and adolescent girls. Our findings also highlight the need to strengthen advocacy against the justification of intimate partner violence and intensify girl-child education.